Cracking the code: a personal journey of learning Glaserian grounded theory - Narayanasamy, Melanie Jay (SAGE, 2017)
My PhD study which began in 2009 focused on the decision-making behaviors of mental health professionals, as they attended a “Single Point of Access” meeting. These meetings are set in community mental health services and involve professionals from an array of professional backgrounds discussing client cases, based on received letters from general practitioners. The general practitioners write these letters seeking advice and direction as to which mental health services the client should be sent to, in response to their needs. On occasions, some general practitioner letters are addressed to a specific person attending the meeting; at other times, they are addressed generally to the whole team. The Single Point of Access meetings house community mental health team members and representatives from more specialized services. The business and interactions of this collection of multidisciplinary professionals provided a useful opportunity to apply a classical grounded theory approach. With Single Point of Access meetings being relatively new at the time of study, discovering, describing, and conceptualizing the decision-making process inherent in these meetings were exciting prospects. After 4 years of study, I produced a grounded theory from my data collection and analysis, which was named “Handling Role Boundaries,” highlighting how these professionals manage and work with multiple roles to bring out the strength of the team and expedite the decision-making process. This case study conveys my personal journey from copious data to Handling Role Boundaries. I present the journey as a learning process, denoted in an “ABCD” format.